Sonifikation. Vermittlungsansätze zwischen Klang und Information - Torsten Roeder (Zeitschrift für digitale Geisteswissenschaften, 2018)
Sonification is the transformation of data into sounds. In the natural sciences, it serves as a supplement to visual interfaces, as an alternative method of analysis, and as an instrument for communicating scientific phenomena. In the Digital Humanities, sonification and its wide range of possibilities has not yet been explored. This paper reports on methodological approaches to sonification, reflects on perceptive and epistemological aspects, and discusses examples from practice. In closing, several possibilities for generating sonification from data will be demonstrated.